PENGARUH PENGAWASAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PEMASARAN PT. INDOFOOD SUKSES MAKMUR. Tbk DI PEKANBARU - Rara Saraswati; Jumiati Sasmita; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine how the variables influence supervision and work environment simultaneously or partially on employee performance marketing PT.IndofoodSuksesMakmur TBK, in Pekanbaru. As for the population in this study is part of a marketing employee PT.IndofoodSuksesMakmur TBK, in Pekanbaru which amounted to 79 people and populations sampled in this study by using the method of census of all employees. Analysis of the data used is descriptive analysis, as it also uses the quantitative analysis using multiple linear regression with SPSS version 18:00. From the results of testing that has been done, simultan regression test (F-test) showed that the supervision and work environment simultan significant effect on employee performance marketing PT. Indofood Sukses Makmur TBK, in Pekanbaru. Partial Test Results (t test) showed that the control variable positive and significant effect on performance, as well as the marketing department employee working environment variable partial positive and significant effect on employee performance marketing.Keywords: Monitoring, Work Environment and Performance.